2009
DOI: 10.1007/s00068-009-8245-7
|View full text |Cite
|
Sign up to set email alerts
|

Base excess determined within one hour of admission predicts mortality in patients with severe pelvic fractures and severe hemorrhagic shock

Abstract: Background: Unstable pelvic ring fractures with exsanguinating hemorrhages are rare but potentially lifethreatening injuries. The aim of this retrospective study was to evaluate whether early changes in acidbase parameters predict mortality of patients with severe pelvic trauma and hemorrhagic shock. Methods: Data for 50 patients with pelvic ring disruption and severe hemorrhage were analyzed retrospectively. In all patients, the pelvic ring was temporarily stabilized by C-clamp. Patients with ongoing bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The higher haemoglobin values in the ethyl pyruvate group compared to the control group also explain the difference with regard to the blood pressure between those two groups at the end of the resuscitation period. Considering that the base deficit is a known indicator for trauma severity, outcome and resuscitation success [ 45 , 49 51 , 12 ], the better recovery in the ethyl pyruvate group underlines the beneficial potential of ethyl pyruvate as resuscitation fluid. Regarding the total protein content and tHb levels, the TxT+H/R_EP group exhibited higher protein values compared to the TxT+H/R_RL group and slightly lower values compared to the sham group (TxT+H/R_RL: 3.32 ± 0.28 g/dL vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher haemoglobin values in the ethyl pyruvate group compared to the control group also explain the difference with regard to the blood pressure between those two groups at the end of the resuscitation period. Considering that the base deficit is a known indicator for trauma severity, outcome and resuscitation success [ 45 , 49 51 , 12 ], the better recovery in the ethyl pyruvate group underlines the beneficial potential of ethyl pyruvate as resuscitation fluid. Regarding the total protein content and tHb levels, the TxT+H/R_EP group exhibited higher protein values compared to the TxT+H/R_RL group and slightly lower values compared to the sham group (TxT+H/R_RL: 3.32 ± 0.28 g/dL vs .…”
Section: Discussionmentioning
confidence: 99%
“…lipopolysaccharide (LPS) and/or damage-associated-molecular-patterns (DAMP) such as HMGB1 caused by tissue damage, notably these hypoxic conditions result in a massive activation of the immune system, which carries a high risk for multiple organ dysfunction syndrome (MODS) and organ failure (e.g. lung, liver) [ 5 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These physiological parameters, which are accounted for in trauma scores, appear to be of the greatest prognostic value when assessed during the first hour after admission, as reported in this issue by Abt et al [7] from the Zurich Trauma Center. As well as physiological scores, anatomical scores are also very important, and combining both scores seems a reasonable approach.…”
mentioning
confidence: 58%
“…Sequential measurements of base deficit and lactate levels in the early phase may help estimating the severity of pelvic hemorrhage. In the study by Abt et al (20), base deficit levels measured within 1 h of admission best predicted severe bleeding and early mortality. Salim et al (21) suggested that a sacroiliac joint disruption, female gender, and the duration of hypotension (systolic blood pressure <100 mmHg) would reliably indicate ongoing bleeding requiring angiographic embolization.…”
Section: Resultsmentioning
confidence: 97%